Temperature response of denitrification rate and greenhouse gas production in agricultural river marginal wetland soils. Issue 3 (9th March 2013) - Bonnett, S. A. F.; Blackwell, M. S. A.; Leah, R.; Cook, V.; O'Connor, M.; Maltby, E.
Abstract Soils are predicted to exhibit significant feedback to global warming via the temperature response of greenhouse gas (GHG) production. However, the temperature response of hydromorphic wetland soils is complicated by confounding factors such as oxygen (O2), nitrate (<inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1x5f271m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−) and soil carbon (C). We examined the effect of a temperature gradient (2–25 °C) on denitrification rates and net nitrous oxide (N2O), methane (CH4) production and heterotrophic respiration in mineral (Eutric cambisol and Fluvisol) and organic (Histosol) soil types in a river marginal landscape of the Tamar catchment, Devon, UK, under non‐flooded and flooded with enriched <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1x5f2725" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3− conditions. It was hypothesized that the temperature response is dependent on interactions with <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1x5f273q" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−‐enriched flooding, and the physicochemical conditions of these soil types. Denitrification rate (mean, 746 ± 97.3 μg m−2 h−1), net N2O production (mean, 180 ± 26.6 μg m−2 h−1) and net CH4 production (mean, 1065 ± 183 μg m−2 h−1) were highest in the organic Histosol, with higher organic matter, ammonium and moisture, and lower <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1x5f2748" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3− concentrations. Heterotrophic respiration (mean, 127 ± 4.6 mg m−2 h−1) was not significantly different between soil types and dominated total GHG (CO2eq) production in all soil types. Generally, the temperature responses of denitrification rate and net N2O production were exponential, whilst net CH4 production was unresponsive, possibly due to substrate limitation, and heterotrophic respiration was exponential but limited in summer at higher temperatures. Flooding with <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1x5f275t" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3− increased denitrification rate, net N2O production and heterotrophic respiration, but a reduction in net CH4 production suggests inhibition of methanogenesis by <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1x5f276c" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3− or N2O produced from denitrification. Implications for management and policy are that warming and flood events may promote microbial interactions in soil between distinct microbial communities and increase denitrification of excess <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1x5f277x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3− with N2O production contributing to no more than 50% of increases in total GHG production.